Briséis et la plainte funèbre de l’épouse dans l’épopée homérique - Marella Nappi (Cahiers Mondes Anciens)
The funeral lament is the type of speech most closely associated with, and representative of, the female voice in the Iliad. In book 19, Briseis, war booty and geras of Achilles, utters such a lament over the dead body of Patroclus. In the preceding book, Patroclus was already the object of several laments, respectively spoken by the Trojan captives (18.28–31, 338–342) and Achilles (18.79–93, 98–126, 324–342). Briseis’lament in book 19 is the first proper female funeral lament in the Iliad which is spoken in the presence of the deceased. It is also Briseis’sole utterance in the entire poem. Briseis is a captive, like the seven women from Lesbos who wail in response to Briseis’lament (19.301) ; and like the captives of Achilles and Patroclus in Book 18. But Briseis is different from the other captives in the Achaean camp, who are mere concubines and remain anonymous as well as silent : alone among the captives Briseis is accorded (by the poet) the privilege of speech. The singularity of the voice of this special captive – special both for Achilles and for the poet – calls for closer inspection. In her lament for Patroclus, Briseis speaks with the voice of someone close to the deceased and assumes the function of the mourning female normally assigned to the mother or wife. Her speaking up can be explained from a ritual as well as from a narrative point of view. Usually, the duty of the funeral lament falls to the closest female family member. In the Greek camp, however, no such female exists. The task of lamentation is delegated to the captive who is the indirect cause of his death and who at present deplores her own solitude. In fact, it is Briseis’own fate as war captive that is foregrounded in her lament. The terms and formulas used to describe her gestures and speech are closely associated with laments triggered by the husband’s death on the battlefield ; when Briseis utters her lament for Patroclus it is the wife’s lament that the poet has in mind. In a sense, Briseis'lament constitutes an update and actualisation of the lamentation she shaved have spoken on the occasion of her husband’s death, before becoming a slave. Clearly, therefore, it is only in comparison with the other ‘mourning voices’ in the Iliad that it is possible to identify the most significant aspects of the mise en scène of Briseis’voice.